The Role and Responsibilities of a Notary in Making a Certificate of Inheritance for Disbursement of Time Deposit Savings Funds by the Heirs - Ibnu Adi Prasetyo; Bambang Tri Bawono; Nanang Sri Darmadi (Sultan Agung Notary Law Review, 2022)
A notary is a public official who authorized to make an authentic deed. Notaries as public officials play an important role in the banking industry, especially in making authentic deeds, one of which is a certificate of inheritance made by a notary. The role and responsibilities of a notary in carrying out his position that a notary is obliged to carry out the provisions contained in the Law on Notary Positions. The approach method used in this research is sociological juridical, meaning that research is carried out on the real situation of the application of law to society with the intent and purpose of finding facts (fact-finding), which then leads to problem identification and then leads to problem solving. Based on research conducted by the author that the role and responsibility of a notary in making a certificate of inheritance rights, a notary in carrying out his position is obliged to follow the provisions contained in the notary position law. Obstacles faced by notaries in making certificates of inheritance rights include notaries not mastering and understanding the provisions related to certificates of heirs, notaries having difficulty determining whether the witnesses presented are appropriate or not, there is no unification regarding the implementation arrangements for making certificates of inheritance rights, there are witnesses or heirs who are dishonest in giving statements. To overcome these obstacles, namely the need for accuracy on the part of the Notary so that mistakes do not occur in the future.